The Impact of Physical Education on Childhood Obesity in Ohio School Children: A Hierarchical Analysis - Nicholas V. Cascarelli Jr.; Karen H. Larwin (Intelektual Pustaka Media Utama, 2017)
Obesity that starts in childhood or adolescence creates greater risk for adult health problems such as heart disease, arthritis, stroke, and cancer. The literature shows that childhood obesity increases most rapidly during the early elementary school years. The current investigation examines the issue of obesity using a systematic stratified random sample of Ohio schools that reported their 3rd grader’s BMI scores for the 2009-2010 school year to the Ohio Department of Health. The sample included 25 schools and 1,006 students. Those schools selected were contacted via phone to ask how many minutes per week schools allocated for physical education in grades K-3, and how many minutes per day was allotted for recess in grades K-3. The analysis also examined potential moderators including the percentage of students receiving free or reduced lunch and the school building academic performance designations as indicated on the Ohio Department of Education webpage. The results suggest that the model run at the student level accounts for approximately 1% of the variation in BMI; the model run at the school level was not a significant predictor of the variance.While the model included for Ohio students did not indicate a strong predictor for childhood obesity, schools can play a significant role in addressing the childhood obesity issue.